A Review on Novel Techniques Used for Drying Medicinal Plants and Its Applications - Ansu Sara Eapen; Yuvraj Khasherao Bhosale; Swarup Roy (International Journal of Biomaterials)
The drying of medicinal plants is a crucial step in their processing since it preserves the active ingredients and increases their shelf life. Traditional drying methods often exhibit limitations such as extended drying time, loss of bioactive components, and decreased product quality. Novel drying methods have recently come to light as possible alternatives for drying medicinal plants. Reduced drying time, greater bioactive ingredient preservation, and improved product quality are just a few benefits of these novel methods. The bioactive components of medicinal plants can be preserved using these modern drying methods, which also provide possibilities for improved processing efficiency, less energy utilization, and increased product stability. However, while choosing a drying method, it is important to take into account the distinctive features of the medicinal plant, the desired quality attributes, and the economic feasibility. This review gives an overview of novel techniques such as microwave drying, vacuum drying, freeze drying, refractance window drying, Osmo drying, supercritical CO2 drying, and spray drying for drying medicinal plants and some potential applications.